Pendekatan Teaching at the Right Level Berbantuan Papan Pintar untuk Meningkatkan Hasil Belajar Piktogram Siswa Madrasah Ibtidaiyah Terpadu Tahfizhul Qur’an Al-Ma’shum Surakarta - Dhiyaa Husnul Khotimah; Praptiningsih; Muhammad Fathurrahman (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
This study aimed to improve fourth-grade students’ mathematics learning outcomes in pictogram topics through the Teaching at the Right Level approach supported by a smart-board learning medium. The study employed classroom action research conducted in two cycles at Madrasah Ibtidaiyah Terpadu Tahfizhul Qur’an Al-Ma’shum, Surakarta. The participants were 15 students from Class IV Thalhah. Each cycle consisted of planning, action, observation, and reflection. Data were collected through learning outcome tests, observations of teacher and student activities, field notes, and documentation. Students were initially assessed and grouped according to three levels of readiness: full understanding, partial understanding, and limited understanding. Learning activities and teacher assistance were then adjusted to each group’s needs. The findings showed continuous improvement across the research stages. The mean score increased from 64.00 in the pre-cycle stage to 73.33 in Cycle I and 88.67 in Cycle II. Classical mastery also increased from 40.00% to 60.00% and finally reached 100.00%. Students became more active in reading, constructing, and interpreting pictogram data through concrete visual activities. The study concludes that integrating ability-based instruction with a smart-board medium can reduce learning gaps and improve students’ conceptual understanding. Its effectiveness depends on accurate diagnostic assessment, flexible grouping, appropriate learning activities, structured assistance, and continuous reflection.